Analysis of Teacher Challenges in the Learning Process for Children with Special Needs - Kirani Lestari; M. Fadlillah; Nihayatul Wafiroh (STKIP Rokania Pasir Pangaraian, 2023)
Children with special needs also get rights and opportunities that are no different from other normal children in the field of education. there are various challenges faced by teachers in teaching children with special needs, for example (1) when making learning tools (2) when delivering material (3) determining appropriate learning methods and media (4) difficulties in student readiness. This study aims to analyze the challenges of teachers in the learning process for children with special needs and also the efforts that can be implemented by teachers in overcoming the challenges faced by teachers. The method in this research is a literature study review by looking for data from various articles or books that are in accordance with the topic of discussion and then reviewed and written on the results and discussion and then concluded. Educating children is not an easy thing especially children who have special needs. As a teacher educator, you must face challenges in teaching children, especially children with special needs, as follows: 1) Requires more time to teach the material so that it is really on the ABK students. 2) Inadequate learning media. 3) Lack of teacher understanding of student characters. 4) Obstacles in delivering the material, because they have to deliver the material in different ways. The efforts that teachers can make to face the challenges of educating children with special needs are as follows: 1) Schools need to complete classroom facilities including learning media so that students can understand the material quickly and can save time. 2) Teachers need to conduct special training so that they can understand the character of students with special needs. 3) Inclusive schools need to prepare GPKs. 4) Pay special attention to children with disabilities. 5) Not only teachers, parents also need to take part in educating their children.